Electrocardiographic markers of myocardial conduction and repolarization in boxer dogs - Carvalho, Elizabeth Regina [UNESP]; Zacché, Evandro [UNESP]; Fenerich, Michelli [UNESP]; Camacho, Aparecido Antônio [UNESP]; Santos, Julio P.; Sousa, Marlos G. (FapUNIFESP (SciELO), 2020)
Carvalho E.R, Zacché E., Fenerich M., Camacho A.A., Santos J.P. & Sousa M.G. 2020. Electrocardiographic markers of myocardial conduction and repolarization in Boxer dogs. Pesquisa Veterinária Brasileira 40(8):630-636. Faculdade de Ciências Agrárias e Veterinárias, Universidade Estadual Paulista “Júlio do Mesquita Filho”, Via de Acesso Prof. Paulo Donato Castellane s/n, Jaboticabal, SP 14884-900, Brazil. E-mail: beth_rcarvalho@hotmail.com Electrocardiographic markers have been used in people to classify arrhythmogenic risk. The aims of this study were to investigate electrocardiographic markers of conduction and repolarization in Boxers and non-Boxer dogs, and compare such findings between groups. Ten-lead standard electrocardiograms of Boxer dogs and non-Boxers recorded from 2015 to 2018 were retrospectively reviewed. Dogs ≥4 years of age and weighing >20kg were included. Animals with valvular insufficiencies, congenital cardiopathies, cardiac dilation, suspected systolic dysfunction, biphasic T-wave, bundle branch blocks, and those receiving antiarrhythmics were excluded. Electrocardiographic markers of conduction, QRS duration (QRSd) and dispersion (QRSD), and repolarization (corrected QT interval, Tpeak-Tend, JT and JTpeak), as well as derived indices, were measured. Two hundred dogs met the inclusion/exclusion requirements, including 97 Boxers (8.1±2.5 years old; 30±7kg) and 103 non-Boxer (8.8±2.5 years old, 30±8kg). QRSd and QRSD, and repolarization markers in lead II and left precordial lead V4 were considered similar between groups. Dispersion of late repolarization on lead rV2, Tpeak-Tend interval, was considered longer in Boxers (45±8ms vs 38±10ms, P=0.01). The Tpeak-Tend/JTpeak and the JTpeak/JT also differed between groups. Our results indicate that the dispersion of myocardial late repolarization in lead rV2 is slower in Boxers than other dog breeds.
Keywords: Arrhythmias; Boxer dogs; Canine; Conduction; Electrocardiography; Myocardium; Premature cardiac complexes; Repolarization